Development of a new ultrasound scoring system to evaluate glandular inflammation in Sjögren's syndrome: an OMERACT reliability exercise - (:unkn) unknown (My University, 2021)
OBJECTIVE: The aim of this exercise from the OMERACT ultrasound subgroup on Sjögren's syndrome (pSS) was to develop and assess the reliability of a consensus-based semiquantitative colour Doppler (CD) ultrasound scoring system for pathologic salivary gland vascularization in patients with pSS. METHODS: Using the Delphi method a CD semiquantitative scoring system for vascularization of bilateral parotid and submandibular glands was developed and tested in static images and on patients (9 pSS patients and 9 sonographers). Intra-reader and inter-reader reliability of grading the salivary glands were computed by weighted Cohen and Light's kappa (κ) analysis, respectively. RESULTS: The consensus-based semiquantitative score was: Grade 0, no visible vascular signals; Grade 1, focal, dispersed vascular signals; Grade 2, diffuse vascular signals detected in < 50% of the gland; Grade 3, diffuse vascular signals in > 50% of the gland. In static images, the intra- and inter-reader reliability showed excellent κ values (95% confidence interval) = 0.90 (0.87-0.93) and 0.80 (0.74-0.84), respectively) for all four salivary glands together. In patients, the intra- and inter-reader reliability for all four salivary glands together was κ  = 0.84 (0.73-0.92) and 0.70 (0.64-0.76), respectively. CONCLUSION: The consensus-based CD ultrasound scoring for the evaluation of salivary gland vascularization in pSS showed a good inter-reader reliability and excellent intra-reader reliability in static images and in patients. The clinical application of the developed scoring system should be tested in clinical settings.
Keywords: scoring system; colour Doppler ultrasound; primary Sjögren’s syndrome; salivary gland vascularization